A Cu-catalyzed four-component cascade reaction to construct β-ester-γ-amino ketones. Issue 23 (24th May 2016) - Ling, Jiayue; Zhang, Jie; Zhao, Yanwei; Xu, Yudong; Wang, Hanghang; Lv, Yuanzheng; Ji, Meishan; Ma, Liang; Ma, Meihua; Wan, Xiaobing
Abstract : Herein, a novel Cu-catalyzed four-component cascade reaction, which encompasses styrenes, diazo reagents, amines, and tert -butyl hydroperoxide (TBHP), was well developed toward β-ester-γ-amino ketones, which showed high chemoselectivity. Abstract : Herein, a novel Cu-catalyzed four-component cascade reaction, which encompasses styrenes, diazo compounds, amines, and tert -butyl hydroperoxide (TBHP), was developed for the synthesis of β-ester-γ-amino ketones. Mechanistically, this transformation was initiated by the interception of an electrophilic Cu-based carbene with nucleophilic α-aminoalkyl radicals, followed by a radical cascade process and an ionic Kornblum–DeLaMare reaction. The methodology was also distinguished by its wide substrate scope, easily available starting materials, and operational simplicity.